1978
DOI: 10.1017/s0043174500064602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Diphenylether Herbicides on Common Purslane(Portulaca oleracea)

Abstract: Nitrofen (2,4-dichlorophenyl-p-nitrophenyl ether) and oxyfluorfen [2-chloro-1-(3-ethoxy-4-nitrophenoxy)-4-(trifluoromethyl) benzene] are 2 diphenylether herbicides which are phytoactive on common purslane(Portulaca oleraceaL.). The stomata of common purslane are normally open during the day and closed at night. Nitrofen and oxyfluorfen applications to common purslane leaves cause the stomata to close which is a result of increased membrane permeability. A slight increase (0.6 C) in leaf temperature and a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Stomatal conductance of the first treated trifoliate, which was fully expanded in both years, was significantly lower than that of untreated plants through 12 DAT (Figure 3). Stomata of common purslane (Portulaca oleracea L.) treated with the diphenylethers, nitrofen [2,4-dichloro-l-(4nitrophenoxy)benzene] and oxyfluorfen [2-chloro-l-(3ethoxy-4-nitrophenoxy)-4-(trifluoromethyl)benzene], closed within 6 h of application and remained closed until leaf abscission (5). By 26 DAT stomatal conductance of treated and untreated soybeans was similar due to reduced conduc tance in untreated plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stomatal conductance of the first treated trifoliate, which was fully expanded in both years, was significantly lower than that of untreated plants through 12 DAT (Figure 3). Stomata of common purslane (Portulaca oleracea L.) treated with the diphenylethers, nitrofen [2,4-dichloro-l-(4nitrophenoxy)benzene] and oxyfluorfen [2-chloro-l-(3ethoxy-4-nitrophenoxy)-4-(trifluoromethyl)benzene], closed within 6 h of application and remained closed until leaf abscission (5). By 26 DAT stomatal conductance of treated and untreated soybeans was similar due to reduced conduc tance in untreated plants.…”
Section: Resultsmentioning
confidence: 99%
“…Stomatal diffusive resistance 5 of plants was determined from one leaflet of the first, second, and third trifoliates of four plants in each plot at approximately the same time every…”
Section: Methodsmentioning
confidence: 99%
“…Working with excised cucumber (Cucumis satiuus L.), Orr and Hess (7,8) showed that after light activation acifluorfenmethyl disrupted cellular membranes causing loss of selective permeability, finally leading to cellular death. Membrane disruption following light activation has also been shown for nitrofen and oxyfluorfen (4,9,12,13).…”
Section: Introductionmentioning
confidence: 82%
“…Chemical agents that are applied often cause damage to agricultural crops, which in some cases are reversible in time, but sometimes lead to irreversible changes in the processes of growth and development of plants which could contribute to their perish (Miller et al, 1963;Martin, Fletcher, 1972;Gorske, Hopen, 1978;Muniyappa et al, 1980;Bakale, 1989;Ferrel et al, 1989;Tripathi et al, 1992;Mukharji, 1994;. Anatomical changes in tissues and organs of crops, degeneration and malformations, reduction of content of chloroplasts in assimilation parenchyma of leaves, which may cause delays in their development may be added to the irreversible changes caused by herbicides (Guh, The purpose of this study was to determine the impact of acetochlor on some anatomic parameters in the leaves of the Oriental tobacco plant.…”
Section: Introductionmentioning
confidence: 99%